ACESSO A MEDICAMENTOS DE ALTO CUSTO POR PROCESSO ADMINISTRATIVO: UM RELATO DE CASO - Locatelli, Cristiane; Cruz, Vanessa E. d.; Konarzewsky, Tamile L.; Bandeira, Vanessa A. C.; Oliveira, Karla R. d. (Salão do Conhecimento, 2013)
Resumo